Evaluation of surgical training at the end of the Urology postgraduate course at the Hospital de Clínicas in Montevideo, Uruguay. - Riverós, Alvaro; Claro, Alexis (Spanish Journal of Medical Education, 2023)
Aim: describe number and type of surgeries realised by a resident along his training during his 4 years in the "Cátedra de Urología del Hospital de Clínicas de Montevideo, Uruguay". Materials and methods: descriptive, longitudinal, retrospective study of the surgical activity developed in the distinct centres of rotation in "Cátedra de Urología del Hospital de Clínicas de Montevideo, Uruguay" during the four years of training of a resident of Urology in the period April 2019 to March 2023. The data were prospective registred in the semmianual portafolio and evaluated number of procedures, subespecialidad of the same, complexity and year of the residence in that they realised . Of the surgeries in which it acted like assistant only registered the total number. Results: During the period analysed the resident participated in a total of 945 surgeries, of which in 744 acted like surgeon, supervised by licenced urologist and in 201 acted like assistant. The average was of 186 surgeries by year, beginning with surgeries of high complexity in second year, being in fourth the year where more realised them arriving to 44 high surgeries. Conclusion: During the postgraduate of Urology the surgical volume increases annualy. It increases not only the number of procedures, but also the complexity of the same, being the last year the one of greater surgical volume.